WAYS TO PREVENT DEPRESSION AND ANXIETY AMONG TEENAGERS (American Journal of Interdisciplinary Research and Development, 2026)
The article scientifically analyzes the role of emotional intelligence (EQ) in preventing depressive states in adolescence. The influence of hormonal changes and psychological crises on emotional instability in adolescence is considered. The main purpose of the study is to substantiate the importance of components of emotional intelligence (self-awareness, emotional regulation, empathy) in increasing adolescent stress tolerance. The author offers theoretical conclusions that prove that adolescents with a high level of emotional intelligence are less prone to depressive symptoms. The purpose of the article is to identify the structural components of emotional intelligence in adolescence and to provide a scientific and theoretical justification for its preventive role in suppressing depressive states. We are considering the possibilities of strengthening the concept of the "I" of a teenager through the development of emotional intelligence and increasing his psychological stability (endurance).